CO2‐responsive CCT protein interacts with 14‐3‐3 proteins and controls the expression of starch synthesis–related genes. (22nd May 2021) - Fukayama, Hiroshi; Miyagawa, Fumihiro; Shibatani, Naoki; Koudou, Aiko; Sasayama, Daisuke; Hatanaka, Tomoko; Azuma, Tetsushi; Yamauchi, Yasuo; Matsuoka, Daisuke; Morita, Ryutaro
Abstract: CO2 ‐responsive CCT protein (CRCT) is a positive regulator of starch synthesis–related genes such as ADP‐glucose pyrophosphorylase large subunit 1 and starch branching enzyme I particularly in the leaf sheath of rice ( Oryza sativa L.). The promoter GUS analysis revealed that CRCT expressed exclusively in the vascular bundle, whereas starch synthesis–related genes were expressed in different sites such as mesophyll cell and starch storage parenchyma cell. However, the chromatin immunoprecipitation (ChIP) using a FLAG‐CRCT overexpression line and subsequent qPCR analyses showed that the 5′‐flanking regions of these starch synthesis–related genes tended to be enriched by ChIP, suggesting that CRCT can bind to the promoter regions of these genes. The monomer of CRCT is 34.2 kDa; however, CRCT was detected at 270 kDa via gel filtration chromatography, suggesting that CRCT forms a complex in vivo. Immunoprecipitation and subsequent MS analysis pulled down several 14‐3‐3‐like proteins. A yeast two‐hybrid analysis and bimolecular fluorescence complementation assays confirmed the interaction between CRCT and 14‐3‐3‐like proteins. Although there is an inconsistency in the place of expression, this study provides important findings regarding the molecular function of CRCT to control the expression of key starch synthesis–related genes. Abstract : CO2 ‐responsive CCT protein (CRCT) is a positive regulator of starch synthesis in vegetative organs of rice. Here we show that CRCT can interact with 14‐3‐3 proteins and controls the transcription of key starch synthesis–related genes such as ADP‐glucose pyrophosphorylase large subunit 1 .